Endolysosomal compartments as platforms for orchestrating innate immune and metabolic sensors. Issue 4 (20th June 2019) - Miyake, Kensuke; Saitoh, Shin‐ichiroh; Sato, Ryota; Shibata, Takuma; Fukui, Ryutaro; Murakami, Yusuke
Abstract: TLRs respond to a variety of microbial products and initiate defense responses against bacteria and viruses. A variety of pathogens invade into and control the endosomal compartment to survive in host cells. On the other hand, host cells deploy cell surface and endosomal TLRs to pathogen‐containing vesicles to mount defense responses. The endosomal compartment is a site for pathogen‐sensing. As TLR‐dependent defense responses are accompanied with a shift to the anabolic state, TLR responses need to be under metabolic control. Cellular metabolic state is monitored by sensing lysosomal metabolites by the mammalian target of rapamycin complex 1 (mTORC1). Type I IFN production induced by endosomal TLRs requires mTORC1. Recent studies have demonstrated that the interaction between TLRs and mTORC1 depends on their anterograde movement to the cell periphery. In a nutrient‐sufficient state, a molecular complex called Ragulator recruits and activates mTORC1 in lysosomes. In parallel, Ragulator allows the small GTPase Arl8b to drive lysosomes to the cell periphery. Nutrient‐activated mTORC1 in peripheral lysosomes is constitutively associated with type I IFN signaling molecules such as TRAF3 and IKKα. On the other hand, TLR7 and TLR3 are activated in the endosomal compartment and induce trafficking of TLR‐containing vesicles to the cell periphery in a manner dependent on Arl8b or another GTPase Rab7a, respectively. Lysosomal trafficking helps TLR7 and TLR3 to interact with nutrient‐activated mTORC1 and type I IFN signaling molecules. The endosomal compartments serve as platforms where metabolic sensing machinery licenses TLRs to initiate type I IFN responses. Abstract : Review on how endosomal compartment actively controls interaction between TLRs and metabolic sensors.